Novel sulfate- and sulfur-reducing bacteria from the Black Sea: metagenomics, enrichment and isolation - van Vliet, Daan M. (2019)
[Excerpt] Background: Anoxic and euxinic marine waters are of importance to the biogeochemistry of modernday ocean as well as the ancient Proterozoic ocean. In these environments, sulfate- and sulfurreducing bacteria (SRB) play a key role through the reduction of oxidized sulfur compounds such as sulfate, thiosulfate and elemental sulfur to sulfide. In previous studies, these marine SRB were found to be comprised of both canonical deltaproteobacterial and non-canonical, mostly uncultured lineages. Objectives: We aimed to test these findings, and to assess the diversity of SRB in the Black Sea, the largest euxinic basin on the planet and a well-studied model ecosystem. [...]